The Logo Analysis from Faculty of Information Technology and Communication of Universitas Semarang in order to Redesign the Logo and the Corporate Identity Design using Logotype Method - Ersyad, Firdaus Azwar; Setya Watie, Errika Dwi; Setyowati, Retno Manuhoro (Jurnal The Messenger, 2018)
The logo analysis from  Faculty  of  Information Technology  and  Communication (FTIK) of Universitas Semarang in order to redesign logo and corporate identity design using logotype method is an effort to stimulate the faculty potentiality, by strengthening the brand image so that faculty is well-known in the future and would convince the society as social partner in organizing education quality. Redesign logo and corporate design is a research and development method which purpose at developing FTIK logo. The research uses Research and Development method. From the entire process of R&D development, eight steps are taken as follow: Potential and Problems of Data Collection, Product Design, Design Validation, Design Revision, Product Trial, Product Revision, Usage Trial, Mass Production. The process of redesigning the logo and faculty identity design refers to the vision and mission of the faculty so it can be implemented in creative concepts, communication strategies and application media.